Representative Council as the Regional Representative Body in the System of the State Administration of the Republic of Indonesia - Mastur Mastur (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
The Regional Representative Council (Dewan Perwakilan Daerah/DPD) is one of new institutions resulting from the amendment of the 1945 Constitution. The Regional Representative Council is one of the representative bodies besides the People’s Representative Council. The Regional Representative Council plays role as a balancing organ of the People’s Representative Council, in order that the function of check and balances in the parliament. DPD as the representative body (Representative) has three functions: legislation function, advisory function, and  supervisory function.  Nevertheless, the role and the function of the Regional Representative Council as one of representative bodies, either from the aspect or the rule of the implementation, has not met the expectation and the goal of the establishment of the Regional Representative Council as the regional representative body. The role and the function of the Regional Representative Council has not been balanced compared to the People’s Representative Council and  has no mechanism of checks and balances. Keywords: Role and function of DPD, Representative body, bicameral